2022
DOI: 10.1186/s12958-022-00987-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for missed abortion: retrospective analysis of a single institution’s experience

Abstract: Objective To explore the risk factors including the difference between mean gestational sac diameter and crown-rump length for missed abortion. Methods Hospitalized patients with missed abortion and patients with continuing pregnancy to the second trimester from Chengdu Women's and Children's Central Hospital from June 2018 to June 2021 were retrospectively analyzed. The best cut-off value for age and difference between mean gestational sac diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A total of 57 titles and abstracts were read based on the inclusion and exclusion criteria. Finally, 15 studies [10][11][12][13]26,[29][30][31][32][33][34][35][36][37][38] were included in this meta-analysis. The literature search flow chart is shown in Figure 1.…”
Section: Study Selections and Basic Characteristics Of Included Studiesmentioning
confidence: 99%
“…A total of 57 titles and abstracts were read based on the inclusion and exclusion criteria. Finally, 15 studies [10][11][12][13]26,[29][30][31][32][33][34][35][36][37][38] were included in this meta-analysis. The literature search flow chart is shown in Figure 1.…”
Section: Study Selections and Basic Characteristics Of Included Studiesmentioning
confidence: 99%
“…Furthermore, the uterus may no longer be enlarged, but instead may contract in size. 1 In recent years, studies have reported that the incidence of missed abortion is on the rise. Allameh et al 2 found that the incidence of missed abortion in clinical diagnosis was 15%-20%.…”
Section: Introductionmentioning
confidence: 99%
“…There may also be symptoms similar to a threatened abortion, such as vaginal bleeding and abdominal pain, but there may even be a complete lack of symptoms. Furthermore, the uterus may no longer be enlarged, but instead may contract in size 1 …”
Section: Introductionmentioning
confidence: 99%
“…Some recognized causes of EA include chromosomal abnormalities, immune factors, endocrine factors, infectious factors, reproductive organ malformations, environmental factors, and maternal behavior and lifestyle. EA can occur at any stage of pregnancy, with 80 % of cases occurring in the early stages [ 3 , 4 ]. There are no effective diagnostic methods for pregnant women at risk of EA or treatments for those with EA.…”
Section: Introductionmentioning
confidence: 99%